Técnicas grafoplásticas en el desarrollo de la creatividad de los niños de educación inicial subnivel II de la Escuela Ciudad de Ventanas - Pazmiño Ruiz, Keily Maily (2023)
Graph-plastic techniques in the teaching-learning process facilitate the work of teachers and students so that they have quality and warmth learning. In the development of the infant's fine motor skills, the case study of how grapho-plastic techniques allow the development of creativity of the initial education children of the “Ciudad de Ventanas” School, Ventanas Canton, Los Ríos Province. The study has a non-experimental and descriptive design. The types of research that were used: descriptive, bibliographic and field research. The methods are: inductive-deductive. The study sample was made up of 43 students and 43 parents at the initial level of the aforementioned institution. The techniques used are a survey of the children's representatives and observation of the children, for which it was necessary to apply a questionnaire with 10 structured questions and a comparison sheet with 6 observable parameters. The results allowed us to conclude that the graph-plastic techniques used by teachers for the development of creativity of the initial education children of the “Ciudad de Ventanas” School are: twisting, crumpling and collage techniques, according to what was declared. For the majority of parents, it was established that the tasks sent home are based on the types of techniques mentioned above, with the purpose of enhancing the creative abilities of the infants.